The influence of biologization of fertilizer systems on the content and stock of humus in a of typical chernozem light loamy - Kucher, L.; Vitvitskyi, S.; Kava, L.; Kucher, T.; Kravchenko, Yu. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2025)
Goal. To investigate the humus state of typical light loamy chernozem and the yield of winter wheat under the conditions of soil protection technologies. Methods. The following methods were used: informative and analytical method for collecting materials from literature sources; field research — observation of plants, accounting and harvesting; laboratory, mathematical and statistical methods — processing of results. The research was conducted on typical coarse-dusty light loam black soil in the forest, the crop was winter wheat, Poliska 90 variety. The comparative effectiveness of the technologies was studied: traditional, based on shelf plowing to a depth of 25—27 cm; soil protection, based on shallow flat-cutting to a depth of 10—12 cm. The effect of fertilization systems was studied against the background of these cultivation technologies: 1 — control (no fertilizers); 2 — straw 1.2 t/ha + N12 + N55P45K45; 3 — straw 1.2 t/ha + N12 + N78P68K68; 4 — straw 1.2 t/ha + N12 + green manure + N55P45K45; 5 — straw 1.2 t/ha + N12 + green manure + N78P68K68. Results. The use of soil protection technology compared to the traditional one did not significantly change the humus content in the arable layer, but affected its redistribution. The highest humus content (3.77%) was recorded in the variant straw 1.2 t/ha + N12+ green manure + N78P68K68 against the background of soil protection technology in the upper soil layer under study. Organic fertilizers increased the content of mobile organic matter in the 0—30 cm layer against the background of plowing by 0.063% relative, and against the background of soil protection technology — by 0.176%. When straw was applied with mineral fertilizers, the content of humic acids in chernozem was typically 0.042—0.052% under conventional technology and 0.055—0.088% under soil protection technology. Conclusions. In the variant with the introduction of straw 1.2 t/ha + N12 + green manure + N78P68K68, the content of humic acids was 1.5 times higher than in the same variant with the traditional technology. Soil protection technology led to an increase in the yield of winter wheat by 3.5 c/ha compared to the traditional technology.